Implikasi Penugasan Jabatan Struktural dan Motivasi Kerja terhadap Performa Pegawai pada Dinas Pendidikan Kota Serang - Farida, R Dewi Mutia; Rosdiana, Rosdiana (Universitas Batanghari Jambi, 2025)
The purpose of this study was to analyze the effect of structural job assignment and work motivation on the performance of employees of the Serang City Education Office. The population and sample in this study were all employees of the Serang City Education Office totaling 65 people. This study used a quantitative method and data collection was carried out through questionnaires distributed to all employees of the Serang City Education Office. The data analysis technique used multiple linear regression. The results of this study revealed that simultaneously and partially there was a positive and significant influence between the variables of structural job placement and work motivation on employee performance at the Serang City Education Office.